2015
DOI: 10.1128/aem.00233-15
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Land Use, Nutrients, and Geography on Microbial Communities and Fecal Indicator Abundance at Lake Michigan Beaches

Abstract: bMicrobial communities within beach sand play a key role in nutrient cycling and are important to the nearshore ecosystem function. Escherichia coli and enterococci, two common indicators of fecal pollution, have been shown to persist in the beach sand, but little is known about how microbial community assemblages are related to these fecal indicator bacteria (FIB) reservoirs. We examined eight beaches across a geographic gradient and range of land use types and characterized the indigenous community structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 56 publications
1
28
0
Order By: Relevance
“…Beach sand samples were analyzed using the Gull2, Lachno2, and HB assays. Selected water and sand samples that were collected from either Point Beach State Park or Kohler-Andrae State Park were also analyzed using the ruminant-specific BacR assay due to the proximal agricultural land use practices (14).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Beach sand samples were analyzed using the Gull2, Lachno2, and HB assays. Selected water and sand samples that were collected from either Point Beach State Park or Kohler-Andrae State Park were also analyzed using the ruminant-specific BacR assay due to the proximal agricultural land use practices (14).…”
Section: Methodsmentioning
confidence: 99%
“…Although recreational waters are the primary monitoring focus for beach managers, numerous studies have documented high concentrations of fecal indicators within beach sand (12,14,32). Recent research has reported the recovery of bacterial and viral human pathogens from beach sand, providing evidence that sand contact may play an important role in beach-associated gastrointestinal (GI) illness (33)(34)(35).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To date, nearly all of the next-generation sequencing studies of sands have focused on sand from marine beaches (2,3,(31)(32)(33)(34)(35), but one recent study has focused on sand from freshwater beaches (17), and due to differences in methodology, including the sequencing platform and biases associated with the sequencing region associated with primer targets (36), the ability to compare these data sets with each other has been limited. In this study, beach sands from 11 beaches throughout the United States, Japan, and South Korea, including 4 beaches from the Great Lakes, were extensively characterized by using Illumina next-generation sequencing of the 16S rRNA gene.…”
mentioning
confidence: 99%
“…Recently, bacterial communities in beach sands have begun receiving increasing attention due to their relevance to public health (4,(13)(14)(15)(16)(17)(18). While recreational waters have long been monitored for indicators of human fecal pollution and their presumed indication of risk to humans because of the presence of human pathogens (19,20), beach sands have historically been neglected in this area.…”
mentioning
confidence: 99%